2023
DOI: 10.3390/ani13132210
|View full text |Cite
|
Sign up to set email alerts
|

Association between Enzootic Pneumonia-like Lung Lesions and Carcass Quality and Meat pH Value in Slaughter Pigs

Abstract: Although the prevalence of respiratory diseases in slaughter pigs ranges from 19% to 74% and continues to be an important concern for swine herds worldwide, only a few studies have investigated the relationship between respiratory disease and pork quality. The general aim of this study was to investigate associations between the prevalence and severity of enzootic pneumonia-like lesions in Polish slaughter pigs on different carcass and meat-quality characteristics at the animal and herd levels. The average pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Our productive analysis revealed that CVPC and dorso-caudal pleurisy could cause substantial weight losses in carcass weight, speci cally 2.77 kg and 2.29 kg in animals with lesions, respectively. These results are in line with other studies investigating declines in carcass weight associated with lung lesions' severity (19,27,(33)(34)(35). The consistency of these ndings across multiple studies and geographical regions underscores the global signi cance of respiratory health in swine production.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our productive analysis revealed that CVPC and dorso-caudal pleurisy could cause substantial weight losses in carcass weight, speci cally 2.77 kg and 2.29 kg in animals with lesions, respectively. These results are in line with other studies investigating declines in carcass weight associated with lung lesions' severity (19,27,(33)(34)(35). The consistency of these ndings across multiple studies and geographical regions underscores the global signi cance of respiratory health in swine production.…”
Section: Discussionsupporting
confidence: 89%
“…The mean prevalence of lesions observed in our study was 23.86% for CVPC and 15.46% for pleurisy. These gures are lower than those reported in previous studies conducted in Poland, where a 45.10% prevalence of macroscopic lung lesions for CVPC at the slaughterhouse was observed (19). However, our study's prevalence falls within the range reported for different European countries, which varies from 19-74%, depending on the source (13,(20)(21)(22)(23)(24)(25).…”
Section: Discussioncontrasting
confidence: 88%